Descomposición de residuos de corteza en la especie forestal eucalipto (Eucalyptus globulus) y evaluación de nutrientes en el producto final - Guevara Cuaspud, Fernando David (2024)
Eucalyptus is one of the most influential wood tree species within the country's industry due to its rapid growth and ability to have multiple yields. The first cut is made at 10 years of age, and subsequent management cuts are made every 5 to 7 years. Among the various eucalyptus varieties, Eucalyptus globulus Labill is the most popular in the Ecuadorian highlands. This variety contains a significant amount of cellulose, and its bark is rich in important nutrients such as nitrogen and phosphorus for plant growth. Unfortunately, not all the eucalyptus trees are harvested entirely, and the bark is often discarded during harvesting or accumulated in companies and sawmills. The filamentous nature of this tree and its inconsistent hardness makes it challenging to handle at an industrial level. This experiment aimed to improve the utilization of eucalyptus by evaluating the performance of bark decomposition through an experimental design to determine the viability of the resulting substrate as a soil improver. In this study, the bark of eucalyptus logs generated by the company NOVOPAN was used. To mitigate bark accumulation, a controlled decomposition process with microorganisms was implemented. Samples were collected for physicochemical analysis, and microorganisms with beneficial characteristics for the decomposition were extracted. These microorganisms were then isolated and inoculated into dry bark chips. The decomposition process was monitored for five months. At the end of the decomposition process, the viability of the substrate was evaluated through laboratory physicochemical analysis. Where the main finding was that microbial activity was not very significant when compared to the non-inoculated control, and the characteristics present in the resulting substrate exhibit a slow release of nutrients, but their structure is favorable for soil and plant development. These results suggest that the microorganisms present in treatments T3 and T4 promote bark decomposition, which could be useful for improving waste management in the wood industry. This research demonstrates that remaining materials from forestry operations are a valuable source of nutrients, despite their slow decomposition.